2020
DOI: 10.1101/2020.10.24.352591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

nearBynding: A flexible pipeline characterizing protein binding to local RNA structure

Abstract: The etiology of diseases driven by dysregulated mRNA metabolism can be elucidated by characterizing the responsible RNA-binding proteins (RBPs). Although characterizations of RBPs have been mainly focused on their binding sequences, not much has been investigated about their preferences for RNA structures. We present nearBynding, an R/Bioconductor pipeline that incorporates RBP binding sites and RNA structure information to discern structural binding preferences for an RBP. nearBynding visualizes RNA structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(93 reference statements)
1
0
0
Order By: Relevance
“…Figure 6b). We also confirmed that double-stranded regions are enriched for RBPs that are known to bind to double-stranded regions such as STAU2 30 , DDX3X 31 , UPF1 32 , and DDX55 33 (Supp. Figure 6b), confirming that our single-cell data captures known patterns from bulk cells.…”
Section: Structural Heterogeneity Can Better Inform Rbp Bindingsupporting
confidence: 69%
“…Figure 6b). We also confirmed that double-stranded regions are enriched for RBPs that are known to bind to double-stranded regions such as STAU2 30 , DDX3X 31 , UPF1 32 , and DDX55 33 (Supp. Figure 6b), confirming that our single-cell data captures known patterns from bulk cells.…”
Section: Structural Heterogeneity Can Better Inform Rbp Bindingsupporting
confidence: 69%